The use of artificial intelligence in tax planning: the new accounting boundary as competitive strategy in firms - Valmor Reckziegel; Edgard Bruno Cornacchione Junior; Jorge de Souza Pinto; Débora Gomes de Gomes (Contabilidad y Negocios: Revista del Departamento Académico de Ciencias Administrativas, 2025)
Firms may have differences in the strategic field, being influenced by internal and external factors to achieve different performance levels. Adopting strategies that guarantee a competitive advantage may result in an improved performance of firms, tax planning being one of them (Maydew, 2001; Hanlon & Heitzman, 2010; Lietz, 2013; Aronmwan & Okafor, 2019; Shevlin, 2020; Sun et al., 2021). Unlike other countries with high taxation and tax complexity, the legitimate management of opportunities to take on taxes can make a firm more competitive in Brazil (Ramos, Niveiros & Carneiro Jr., 2019). In the technological development field, studies present artificial intelligence as a strategic tool to improve the decision-making process in various structured situations (Silva, Costa & Pimenta, 2022; Li et al., 2024; Rafik, 2024; Belahouaoui & Attak, 2024; Krupa & Mullaney, 2024). Therefore, the research question is: How is artificial intelligence presented in business management studies, particularly in the best tax decision, given the different scenarios and administrative complexity in Brazil? The aim thereto is to develop theory on research on artificial intelligence in business management studies, especially in tax planning aiming at the best option in the scenario reducing taxation and, consequently, at improving the company performance. The methodology used was exploratory and documentary, doing research in national and international journals. Using the following keywords: artificial intelligence, tax planning and accounting, forty-six relevant studies on the matter were identified in data bases like Scopus, Web of Science and CAPES gazettes; literature on the research subject was analyzed, and findings evidence a clear gap in the use of artificial intelligence in tax planning studies.